THE INFLUENCE OF MANGANESE ON THE TENSILE STRENGTH OF HIGH CARBON STEEL C66D - Aida Imamović; Omer Kablar; Mirsada Oruč; Vedina Purić-Selimović; Lamija Sušić (Journal of Sustainable Technologies and Materials)
Modern steel production cannot be imagined without manganese, because almost all steels contain manganese.In this paper, we present the impact of manganese on the tensile strength values of high-carbon steel. This paper presents an improvement in the quality of wire rolling with control of manganese content in steel and the value of C-equivalent, in industrial conditions, which is of particular importance in the production of this quality of steel. For the presented quality of rolled wire made of high-carbon steel, it is possible to control the C-equivalent in high-carbon steel to achieve values for tensile strength in exceptionally narrow tolerances of 1000 ± 30 MPa.